Friction and wear of multiple steel wires in a wire rope - Yuxing Peng; Kun Huang; Chenbo Ma; Zhencai Zhu; Xiangdong Chang; Hao Lu; Qing Zhang; Chunming Xu (Friction)
Abstract The fretting wear among the steel wires aggravates the wire rope’s fatigue damage, affects the service performance of the wire ropes, and threatens mine hoisting safety. In this paper, the practical friction behavior and wear mechanism among the wires in the wire rope are investigated. A series of tests were carried out on multiple steel wires in helical contact and tension-torsion coupling under different fretting parameters, twisting parameters, and lubrication conditions by self-made friction and wear testing machine. The results show that the coefficient of friction (COF) among the steel wires decreases slightly with increasing lateral loads and tension, and the effect of twist angle on the COF has opposite results under different lubrication conditions. Lateral loads, tension of the steel wires, twist angle, and lubrication condition all affect the fretting morphology among the steel wires. Fretting wear with larger twist angle structure leads to more energy loss. The energy loss of fretting is directly related to the fretting morphology among the contact surfaces, and the dissipated energy is lower in the two forms of complete slip and sticking. The wear depth and width increase with the increase of lateral loads, steel wire tension, and twist angle. And the wear width and depth under dry friction conditions are higher than those under oil lubrication conditions. In addition, the wear mechanism under dry friction conditions is mainly abrasive wear, adhesive wear, and fatigue wear. And the wear mechanism under oil lubrication conditions is mainly abrasive wear and fatigue wear.